2015
DOI: 10.1021/jacs.5b01457
|View full text |Cite
|
Sign up to set email alerts
|

A Gold@Polydopamine Core–Shell Nanoprobe for Long-Term Intracellular Detection of MicroRNAs in Differentiating Stem Cells

Abstract: The capability of monitoring the differentiation process in living stem cells is crucial to the understanding of stem cell biology and the practical application of stem-cell-based therapies, yet conventional methods for the analysis of biomarkers related to differentiation require a large number of cells as well as cell lysis. Such requirements lead to the unavoidable loss of cell sources and preclude real-time monitoring of cellular events. In this work, we report the detection of microRNAs (miRNAs) in living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
149
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(161 citation statements)
references
References 52 publications
6
149
0
Order By: Relevance
“…4 Recently, polydopamine was found to be fluorescent under certain conditions. For example, Zhang and co-workers obtained fluorescent polydopamine (FPD) nanoparticles (NPs) by treating polydopamine with concentrated H2O2.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, polydopamine was found to be fluorescent under certain conditions. For example, Zhang and co-workers obtained fluorescent polydopamine (FPD) nanoparticles (NPs) by treating polydopamine with concentrated H2O2.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al showed that polydopamine (PDA) coated GNPs have much better stability in cells and can track miR-29b and miR-31 (involved in differentiation progress of human mesenchymal stem cells) simultaneously for five days 122 . In detail, they coated polydopamine (PDA) on GNPs and further adsorbed β-hairpin DNA through π-π interactions.…”
Section: Probes Imaging Endogenous Rnasmentioning
confidence: 99%
“…In detail, they coated polydopamine (PDA) on GNPs and further adsorbed β-hairpin DNA through π-π interactions. In the absence of target miRNAs, the fluorescence of β-hairpin DNA was totally quenched by both GNPs and PDA, but in the presence of target miRNAs, the β-hairpin DNA detached from the PDA surface and bound with target miRNAs, restoring fluorescence 122 .…”
Section: Probes Imaging Endogenous Rnasmentioning
confidence: 99%
“…First, we prepared bare AuNPs (60 nm) by ac onventional seed-growing method. Tw op robes were synthesized for different targeting purposes.I nS cheme 1b,C y5-labeled consensussite double-stranded DNA(ds-DNA, with aspecial sequence to target the central domain of the p53 protein) was immobilized onto the PDAshell through p-p interactions, [10] forming Probe 1. [8] Next, DAPB molecules were conjugated on the PDAshell by reversible bonding between the catechol groups of PDA and boronic acids.…”
mentioning
confidence: 99%